Modern Methods and Their Applications to Strong Gravitational Lensing - Maresca, J (2023)
This thesis presents a collection of works, some methodological and others observational, with the common theme of strong gravitational lensing. We have leveraged a wide variety of techniques, from machine learning algorithms to uv-plane modelling, and used a multitude of simulated and real data products to achieve the results contained within this thesis.